Elevated Inflammatory Markers in COVID-19 Patients in Relation to Symptom onset and Antiviral Therapy Options - Kevin Dermawan; Nurhayati Adnan (Jurnal EduHealth, 2023)
The COVID-19 virus has become a terrible global pandemic and has even caused severe trauma for all citizens in the world. Even though the number of cases is starting to decline, mutations of this virus are still possible and management is important to prevent serious fatalities. CRP and D-dimer have been widely studied as good markers of COVID-19 inflammation, and their application can even be used as a predictor of symptom severity. The rapid replication of the virus makes starting antiviral therapy from the onset of infection very crucial. Many previous studies have associated a worse prognosis in patients who receive antiviral therapy more slowly. The choice of antiviral is also important in order to effectively reduce viral replication and reduce the patient's severity. This study aims to compare the onset of symptoms and the choice of antiviral therapy in relation to suppressing the increase in inflammatory markers, namely CRP and D-dimer. This study uses a retrospective cohort model with a simple random sampling method that collects data on patients with COVID-19 who underwent treatment at a private hospital in Tangerang during the period January – December 2021 with a complete examination of CRP and D-dimer at the time the patient first arrived and on the day of the birth. 5 treatments. Data collected included age, gender, history of hypertension, diabetes mellitus, antiviral therapy used, onset of symptoms when the patient came to the hospital and CRP and D-dimer lab values. All of this data was then analyzed bivariately using the paired T test or Wilcoxon test method to determine the statistical significance of the data. The number of research subjects was 84 patients with an average age of 45.20 ± 15.02 years. Of all the patients, 14 patients had severe symptoms and 2 of them died. The CRP value at the time the patient first arrived was found to be lower in patients who came with symptom onset ≤ 2 days compared to those with symptom onset > 2 days with values respectively 12.55 and 33.01 mg/L, P value = 0.005. The D-dimer values in the two groups were also significantly different with values of 379.68 and 720 ng/mL, P value = 0.005. Based on the symptom onset category, it was found that patients who received antiviral therapy with symptom onset ≤ 2 days were found to have no significant differences in CRP and D-dimer values between the first day and the 5th day of treatment. This shows the effectiveness of the therapy provided. However, the group of patients who received antiviral therapy after the onset of symptoms > 2 days had significantly higher CRP and D-dimer values. The CRP values for the first day and the 5th day were 33.00 and 42.66 with a P value = 0.008 and the D-dimer values were 720 and 835.03 with a P value = 0.0029. In selecting the antiviral used, it was found that the remdesivir group provided a better prognosis with CRP values of 31.30 (H-1) and 40.93 (H-5), P value = 0.39. However, the same as favipiravir there was still a significant increase in D-dimer. Thus, starting antiviral therapy early with symptom onset ≤ 2 days is better for patient prognosis. The therapy chosen can be assumed to be that remdesivir is more effective than favipir avir in suppressing the increase in inflammatory markers, namely CRP and D-dimer.